BEYOND GRAMMAR: BUILDING CONFIDENCE AND CLARITY IN STUDENT WRITING (HIGHER EDUCATION) (Scientific journal of the Fergana State University, 2024)
This study examines the factors beyond grammatical competence that contribute to building confidence and clarity in student writing within higher education. By analyzing the interplay between students' self-efficacy, feedback mechanisms, and writing practices, this research aims to identify effective strategies for enhancing writing skills. Utilizing a mixed-methods approach, the study incorporates surveys, interviews, and textual analysis to explore the experiences and perceptions of students and educators. The findings highlight the importance of supportive feedback, practical writing exercises, and confidence-building activities in fostering clear and effective writing. This research provides actionable insights for educators seeking to improve student writing outcomes.